Annual Plan Proposals 1993-94 Government of Kerala - Planning Commission (Planning Commission, 1992)
The efforts initiated during the current year to overhaul planning and the procedures connected with it, with emphasis on rationalising plan expenditure weeding out uneconomic schemes, and mobilisation of resources from extra budgetary sources, would be continued with vigour during 1993-94. Keeping the national goals and approaches in view and. taking into account the need to step up over-all investment and productive sectors in Kerala, participatory planning through people’s involvement, and by enlisting private sector investment in industry and power in a major way, is contemplated. In Agriculture, the government agencies would give particular attention to reverse the declining trend in the use of credit from the co-operative sector and financial institutions, and propagate intensive cropping. Given below is a brief outline of the State Plan part of the overall development effort proposed for 1993-94.
State Planning Board Thiruvananthapuram